2007
DOI: 10.1016/j.jinsphys.2006.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Diapause-specific gene expression in the northern house mosquito, Culex pipiens L., identified by suppressive subtractive hybridization

Abstract: In this study we probe the molecular events underpinning diapause observed in overwintering females of Culex pipiens. Using suppressive subtractive hybridization (SSH) we have identified 40 genes that are either upregulated or downregulated during this seasonal period of dormancy. Northern blot hybridizations have confirmed the expression of 32 of our SSH clones, including 6 genes that are upregulated specifically in early diapause, 17 that are upregulated in late diapause, and 2 upregulated throughout diapaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 62 publications
7
91
1
7
Order By: Relevance
“…More recently, the up-regulation of TCP-1 has been associated with cold hardiness in the onion maggot, D. antiqua (54), and has also been implicated in diapause of the brine shrimp, A. franciscana, where it is found in association with microtubules in undeveloped cysts (55). A link between microtubule stability and cold survival is noted in several poikilotherms adapted to cold environments (56)(57)(58), and a range of cytoskeletal adjustments are associated with insect diapause (25,(59)(60)(61). Our data, showing the upregulation of a microtubule-specific chaperonin during diapause, further highlight the importance of cytoskeletal stability during diapause and low-temperature survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the up-regulation of TCP-1 has been associated with cold hardiness in the onion maggot, D. antiqua (54), and has also been implicated in diapause of the brine shrimp, A. franciscana, where it is found in association with microtubules in undeveloped cysts (55). A link between microtubule stability and cold survival is noted in several poikilotherms adapted to cold environments (56)(57)(58), and a range of cytoskeletal adjustments are associated with insect diapause (25,(59)(60)(61). Our data, showing the upregulation of a microtubule-specific chaperonin during diapause, further highlight the importance of cytoskeletal stability during diapause and low-temperature survival.…”
Section: Discussionmentioning
confidence: 99%
“…Clones of most newly identified Hsps reported in this study were obtained by suppressive subtractive hybridization (SSH), subtracting cDNA from nondiapausing pupae (5 d after pupariation, the developmental stage equivalent to diapause) from that of pupae that had been in diapause for 20 d, as described for the mosquito Culex pipiens (61). Briefly, RNA pools from 20 individuals were created by using TRIzol Reagent (Invitrogen, Carlsbad, CA), cDNA was synthesized by using the BD SMART PCR cDNA Synthesis kit (BD Biosciences, Franklin Lakes, NJ), and the subtraction was achieved by using a BD PCR-Select cDNA Subtraction kit (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…In D. montana we found significant enrichment for actin filaments/muscle protein, while in D. virilis we found significant enrichment for several clusters of genes involved in protein signalling/modification (Table 1). Changes in actin filaments /muscle protein have previously been implicated in insects to prevent cold injury by preventing the depolymerisation of the cell membrane during diapause (Kim et al, 2006;Robich et al, 2007;Koštál, 2010). Thus, these changes may help to maintain cellular physiology at suboptimal temperatures.…”
Section: Functional Processesmentioning
confidence: 99%
“…Several classes of genes up-regulated as well as down-regulated in the diapause have been identified using suppresive substractive hybridisation (SSH) and microarray (Xia et al 2007). Robich et al (2007) identified 32 diapause related genes, which were specifically expressed during dormancy in Culex pipiens. Among these, the expressions of PABP gene remained unchanged throughout the diapause period of C. pipiens.…”
Section: Metabolic Enzyme Genes and Translational Regulatory Gene Expmentioning
confidence: 99%
“…There is a sufficient database available that describes the physiological features of diapause, its environmental regulation and the hormonal control mechanism (Hahn and Denlinger 2010). Robich et al (2007) studied the molecular mechanism of diapause in Culex pipiens and identified 32 genes that were either up-regulated or down-regulated during the early, late or throughout dormancy. The embryonic development in B. mori is interesting because in certain races, embryonic development precedes uninterrupted (non-diapause), while in some, it is characterized by the diapause.…”
Section: Introductionmentioning
confidence: 99%